Gedemilitariseerde sones: ’n Doeltreffende konflikbeslegtingsmetode? - Coetzer, W.J.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
It is assumed that demilitarized zones serve a useful purpose in physically dividing fighting factions. In this article the author advocates the point that in practice, demilitarized zones become nothing more than substitutes for final political solutions. He also maintains that demilitarized zones tend to worsen rather than defuse the conflict situation.